A trinuclear cobalt coordination complex constructed using novel triazine ligands via one-pot green synthesis: structural properties and biological evaluation. (24th March 2023) - Parveen, Sheikdawood; Premkumar, Thathan; Nguyen, Hung-Huy; Govindarajan, Subbiah
Abstract : A triazine-based trinuclear cobalt complex, synthesised via a one-pot green synthesis process, exhibits unique structural behaviours and excellent biological activities. Abstract : New triazine ligands C3 H5 N5 O (L1 ) and C5 H5 N5 O3 (H2 L2 ) were synthesised by reacting diaminoguanidine hydrochloride and glyoxylic acid in 1 : 1 and 1 : 2 molar ratios, respectively, at 150 °C in a green solvent (water). The corresponding cobalt complex, [Co3 (L1)2 (L2)4 ]·4H2 O (1 ), was synthesised via a one-pot green synthesis process and was subsequently characterised by spectroscopic and elemental analysis methods. The structure of the cobalt complex was determined via single crystal X-ray diffraction analysis. Two types of ligands were observed in the cobalt complex: neutral (L1 ) and anionic (H2 L2 ) ligands. The asymmetric unit was composed of one and a half crystallographically independent Co atoms, one L1 and two L2 2 − ligands, and two lattice water molecules. Interestingly, the core structure of the complex had a neutral mixed-valence Co(iii )–Co(ii )–Co(iii ) trimer, and the overall neutrality of the complex was achieved because of the di-ionic nature of the H2 L2 ligand. The spectral, thermal, and biological properties of the complex were explored, and biological aspects, such as antioxidant activity, protein binding and cytotoxicity, were examined. An assessment of the antioxidant activity of the compounds indicated better scavenging activity against ABTS˙ +, DPPH˙, O2 −, and NO˙ radicals than the known scavengers butylated hydroxyl anisole and ascorbic acid. The cobalt complex showed potential cytotoxicity toward MCF-7 cancer cells and was capable of inducing apoptosis.